Survey of five major grapevine viruses infecting Blatina and Žilavka cultivars in Bosnia and Herzegovina - Crnogorac, Ana; Panno, Stefano; Mandić, Ana; Gašpar, Mladen; Caruso, Andrea Giovanni; Noris, Emanuela; Davino, Salvatore; Matić, Slavica (PloS one, 2021)
The sanitary status of grapevines has not yet been considered sufficiently in vineyards throughout Bosnia and Herzegovina (BiH). An extensive survey of five major grapevine viruses in the country was carried out in 2019. A total of 630 samples from the two dominant autochthonous cultivars, named Žilavka and Blatina, were tested by DAS-ELISA for the presence of grapevine leafroll-associated viruses (GLRaV-1 and 3), grapevine fleck virus (GFkV), grapevine fanleaf virus (GFLV) and Arabis mosaic virus (ArMV). Eighty-eight % of the samples were positive for at least one virus, and all five viruses were detected, thought with different incidence, i.e. GLRaV-3 (84%), GFLV (43%), GLRaV-1 (14%), GFkV (10%) and ArMV (0.2%). The majority of infected plants (about 75%) were asymptomatic. Specific virus symptoms were observed in the remaining infected plants, together with the reported GLRaV vectors, Planococcus ficus and Parthenolecanium corni , while nematodes of the Xiphinema genus were not found in the GFLV- or ArMV-infected vineyards. The GLRaV-3 CP phylogenetic analyses showed 75–100% nucleotide identity between the BiH and reference isolates, and the BiH isolates clustered into the major group. The dNS/dS ratio indicated a negative selection of the virus population, and the lack of geographical structuring within the population was observed. In addition, putative GLRaV-3 recombinants with breakpoints in the 5’ of the CP gene were detected, while no recombinant strains were identified for the other four viruses. The obtained results indicate a deteriorated sanitary status of the cultivated grapevines, the prevalence and intraspecies genetic diversity of GLRaV-3 throughout the country. The establishment of certified grapevine material and adequate virus vector control is therefore of primary importance to prevent further spread of these viruses. This study presents the results of the first molecular characterisation of grapevine viruses in Bosnia and Herzegovina.